Active learning units interrelated using TIC’s tools in architectural construction - Núria Martí Audí; David Fonseca Escudero (Education in the Knowledge Society, 2013)
<!--[if gte mso 9]> 0 0 1 141 779 USAL 6 1 919 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> The presence of new technologies in the university world is a matter of fact. Nevertheless, it has not always blended correctly as in many cases TIC incorporation has not taken alumni opinion understood as final users. A correct implementation might evaluate some variables as satisfaction, need, interest and finally that versatility to adapt it to proficient professional training on a regular basis. This paper analyses a new approach to learning in the field of Architectural Construction based on a series of strategically designed and interactive units. The centre of these is the collaborative project; this is based on complex problem-solving situations akin to the professional world; where theory and practice are combined in a discovery-learning process. The tools of Information and Communication Technology are applied, simultaneously facilitating the student’s autonomy in acquiring skills and knowledge. <!--EndFragment-->